Optimization ultrasonic-assisted aqueous two-phase extraction of glabridin from licorice root and its activity against the foodborne pathogen MRSA - Qianwei Qu; Zhenxin Zhu; Mengmeng Zhao; Huiwen Wang; Wenqiang Cui; Xingyu Huang; Zhongwei Yuan; Yadan Zheng; Na Dong; Yanyan Liu; Haoran Wang; Chunliu Dong; et al. (Food Chemistry: X)
This study aimed to extract glabridin (GLA) from licorice using an environmentally sustainable ultrasonic-assisted aqueous two-phase extraction method and to evaluate its efficacy. The extraction parameters were optimized through single-factor experiments and response surface methodology, resulting in a GLA content of 2049.51 μg/g under the conditions of 51 min ultrasonic time, 76 °C ultrasonic temperature, and 640 W ultrasonic power. In vitro analyses demonstrated that licorice extract (1.6 mg/mL) and GLA (8 μg/g) exhibited rapid bactericidal activity against methicillin-resistant Staphylococcus aureus (MRSA). Furthermore, both licorice extract and GLA showed significant disinfection activity against MRSA in models of pork spoilage and cooking utensils. Mechanistic studies revealed that GLA targets phospholipids, thereby disrupting the integrity and normal function of bacterial cell membranes. In conclusion, this study introduces an environmentally sustainable and effective method for obtaining a GLA-rich extract from licorice, which has potential applications in the food industry for addressing MRSA contamination.